1-[4-Fluoro-2-(2-nitrovinyl)phenyl]pyrrolidine Suppresses Toll-Like Receptor 4 Dimerization Induced by Lipopolysaccharide. Issue 3 (3rd May 2016) - Ahn, Sang-II; Kim, Ji-Soo; Hong, Chae-Yeon; Gu, Gyo-Jeong; Shin, Hyeon-Myeong; Jeong, Hyun Jung; Koh, Kwang Oh; Mang, Joo Yang; Kim, Dae Young; Youn, Hyung-Sun
Abstract : Toll-like receptor 4 (TLR4) recognizes LPS and triggers the activation of the myeloid differential factor 88 (MyD88)- and toll-interleukin-1 receptor domain-containing adapter, inducing interferon-β (TRIF)-dependent major downstream signaling pathways. Previously, we presented biochemical evidence that 1-[4-Fluoro-2-(2-nitrovinyl)phenyl]pyrrolidine (FPP), which was synthesized in our laboratory, inhibits NF-κB activation induced by LPS. Here, we investigated whether FPP modulates the TLR4 downstream signaling pathways and what anti-inflammatory target in TLR4 signaling is regulated by FPP. FPP inhibited LPS-induced NF-κB activation by targeting TLR4 dimerization. These results suggest that FPP can modulate the TLR4 signaling pathway at the receptor level to decrease inflammatory gene expression.